Effect of Current Stressing on Mixed Solder Joint Resistance and Temperature - Muhammad Nubli Zulkifli,; Izhan Abdullah,; Muhammad Fathullah Ahmad Azam ,; Nurul Hanis Azhan,; Afaq Ahmed,; Azman Jalar, (International Journal of Integrated Engineering, 2024)
This paper aims to investigate the impact of current stress on the electrical performance of mixed solder joints made of SnPb with SnCu and SnPb with SAC305. This information is currently missing and requires further research. The resistance of current-stressed pin-through-hole (PTH) solder joints, namely SnPb, SnCu, SAC305, and mixed solder joints of SnPb/SnCu and SnPb/SAC305, was measured using a micro-Ohm meter based on the Kelvin method. Temperature measurements were conducted by attaching two thermocouple probes to the solder joints. A microstructure examination was performed on the cross-section sample of PTH solder joints and further analyzed using open-source image processing software, ImageJ. It is noteworthy that fully mixing leaded and lead-free solder can reduce the variation of resistance during the application of current. The resistances of SnCu solder joints vary more compared to those of SAC305 joints with increasing applied current. Resistance variation of the SnPb/SnCu mixed solder joint is more dominant towards the SnPb solder joint trend, whereas SnPb/ SAC305 mixed solder joint is more dominant towards the SAC305 solder joint trend. The findings obtained from the ImageJ software analysis can be utilized to examine the evolution of microstructure and its correlation with the electrical properties of mixed solder joints.